Comprehensive evaluation of combining CFD simulation and entropy weight to predict natural ventilation strategy in a sliding cover solar greenhouse - Li, He; Ji, Dong; Hu, Xi; Xie, Tian; Song, Weitang; Tian, Subo (International Journal of Agricultural and Biological Engineering, 2021)
This study proposed a comprehensive evaluation system to incorporate the contribution of both numerical simulation and statistical decision theory in ventilation performance assessment. A high-resolution model based on the finite volume approach was established to analyze the influence of rotation angles (i.e., side vent flip angle and roof vent flip angle) of the rack-and-pinion ventilated structure on the greenhouse microclimate. The water circulating system and tomato seeding canopies were considered. Heat removal efficiency and mean age of air were employed as quantitative attributes to reflect the internal thermal environment and the airflow organization in the sliding cover solar greenhouse. The simulation model was verified with the temperature profile measured and the average relative error was 1.74%. The results demonstrate that the rotating angles of ventilation schemes have a substantial impact on the microclimate and inhomogeneity of the tomato seeding canopies. The results suggest the average velocity and its inhomogeneity are the crucial predictors, and their entropy weight values are 0.231 and 0.218, respectively. The relative degree of membership of the side vent flip angle of 45° is 36% and 97% higher than that of the side vent flip angle of 35° and the side vent flip angle of 25°, respectively. This study can provide a reference to evaluate the ventilated strategies of the sliding cover solar greenhouse for the regional and central government.Keywords: sliding cover solar greenhouse, natural ventilation, CFD simulation, entropy weight, comprehensive evaluationDOI: 10.25165/j.ijabe.20211406.6793Citation: Li H, Ji D, Hu X, Xie T, Song W T, Tian S B. Comprehensive evaluation of combining CFD simulation and entropy weight to predict natural ventilation strategy in a sliding cover solar greenhouse. Int J Agric & Biol Eng, 2021; 14(6): 213–221.